Single-Argument Clause in Bahasa Indonesia - Ida Ayu Putu Aridawati; I Wayan Sudiartha; Ida Bagus Rai Putra; Ni Putu N. Widarsini; I Wayan Teguh; I Ketut Nama; I Gede Bagus Wisnu Bayu Temaja (Westscience Press, 2024)
A previous study was conducted on types of clauses or sentences in Bahasa Indonesia. This study attempted to focus more on the clauses constructed by a single argument in BI. The data were collected from BI speakers, literature, and the researchers' intuition as BI speakers. Data analysis was implemented using a descriptive method. The results found that BI has several clauses, such as intransitive, antipassive, stative, and passive. However, BI owns no non-stative and split transitive clauses. It can be shown that affixes in BI play a significant role in determining types of construction, particularly in the passive. As one of the agglutinative languages, BI shows its property, in which affixed occurred.